ANALISIS PERBANDINGAN DISTRIBUSI ZAKAT PRODUKTIF DAN KONSUMTIF DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA PEKANBARU TAHUN 2011-2020 - Ramnah Siregar; Rosyetti Rosyetti; Rahmat Richard (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to determine and analyze the difference in the average distribution of productive and consumptive zakat in BAZNAS Pekanbaru City in 2011-2020. By knowing the difference in the average distribution of zakat and analyzing which one is more effective and efficient in overcoming poverty so that the distribution can achieve the goal of zakat, namely to prosper and reduce poverty. The analytical method used in this study is a non-parametric statistical analysis technique using the Wilcoxon rank sum test level test to see the difference in the average distribution of productive and consumptive zakat which is calculated manually with the help of Microsoft Excel. The results show that there are differences in the average distribution of productive and consumptive zakat in BAZNAS Pekanbaru City, this is because Pekanbaru City BAZNAS is more focused on the distribution of consumptive patterns than productive ones. It can be seen from the number of superior programs of Pekanbaru City BAZNAS, namely the distribution in the consumptive pattern has four superior programs while the productive pattern is only one superior program.